Peran Saudara Kandung terhadap Permasalahan Gizi Balita di Lingkungan Keluarga - Yunita Wulandari; Evi Martha (Universitas Malahayati Lampung, 2025)
ABSTRACT Nutritional problems in toddlers are influenced by various factors. The presence of siblings is one of the factors that play a role in the nutritional problems of toddlers. Close birth distance causes the care of children in one family to be not optimal. Find out the causes of under-five nutritional problems among siblings in the same family.The study used a systematic review method using PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis). Material collection was carried out using two search engines, Google Scholar and Science Direct, which were accessed via https://remote-lib.ui.ac.id/. 1250 articles from Google Scholar and 63 articles from Science Direct were obtained. Eight articles were reviewed. Keywords used